MILITARY QUOTATION IN DISCIPLINARY ETHICAL PROCEDURES: COMPLIANCE WITH COMPLIANCE WITH ARTICLE 358 OF THE CRIMINAL PROCEEDINGS, AVOIDING ARGUATION OF NARROWS IN CASE OF LARGE DEFENSE AND CONTRADICTORY (Fiep Bulletin - online, 2020)
This article offers the members of the various Ethics Commissions of the CONFEF / CREFs System, strict compliance with the Principle of Legality, when notifying cited Complainants in Disciplinary Ethical Processes (PEDs) when they are Military, and must be complied with. the precept of art. 358 of the Code of Criminal Procedure, in the future avoiding the nullity argument, especially if it is considered revel, given that the summons was sent to his residence and not to his domicile.
Keywords: Ethics; Citation; Nullity